2015
DOI: 10.1111/sode.12151
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Stress Symptoms in Children Exposed to Intimate Partner Violence: The Role of Parent Emotion Socialization and Children's Emotion Regulation Abilities

Abstract: Exposure to intimate partner violence (IPV) is a traumatic life event. Almost 50 percent of IPV‐exposed children show subsequent post‐traumatic stress symptoms (PTSS), and they are at increased risk for depression. We examined maternal emotion socialization and children's emotion regulation as a pathway that may protect IPV‐exposed children from developing PTSS and depression. Fifty‐eight female survivors of IPV and their 6‐ to 12‐year‐old children participated. Results showed no direct relations between mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 61 publications
3
22
0
1
Order By: Relevance
“…It is unclear whether the same associations and pathways would be replicated in a more racially or culturally diverse group (e.g., Morelen, Jacob, Suveg, Jones, & Thomassin, 2013). Future studies could also explore the potential impact of socioeconomic status or other risk factors (for examples of such work, see Fainsilber Katz et al, 2016, andZeman, Dallaire, &Borowski, 2016); diversity in family composition (for a study of ES in single mother headed households, see McKee et al, 2015); and other socializing agents such as siblings, peers, and educators (see, e.g., Klimes-Dougan et al, 2014) on ES processes. Additionally, although we solely considered parental responses to expressions of negative affect in the present study, many other parenting behaviors (e.g., parenting style, disciplinary approach) may be associated with the examined outcome variables (Parisette-Sparks et al, 2017) and could be explored in future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear whether the same associations and pathways would be replicated in a more racially or culturally diverse group (e.g., Morelen, Jacob, Suveg, Jones, & Thomassin, 2013). Future studies could also explore the potential impact of socioeconomic status or other risk factors (for examples of such work, see Fainsilber Katz et al, 2016, andZeman, Dallaire, &Borowski, 2016); diversity in family composition (for a study of ES in single mother headed households, see McKee et al, 2015); and other socializing agents such as siblings, peers, and educators (see, e.g., Klimes-Dougan et al, 2014) on ES processes. Additionally, although we solely considered parental responses to expressions of negative affect in the present study, many other parenting behaviors (e.g., parenting style, disciplinary approach) may be associated with the examined outcome variables (Parisette-Sparks et al, 2017) and could be explored in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Magnifying responses have been found to be correlated with internalizing and externalizing symptoms and behavioral avoidance (Eisenberg et al, 1998;Silk et al, 2011). Lastly, rewarding responses to negative emotion have predominantly, but inconsistently, been associated with positive socioemotional development, with rewarding responses to youth expressions of sadness and anger inversely related to internalizing symptoms, whereas reward of youth expressions of fear has been linked to greater internalizing behavior (Eisenberg et al, 1998;Fainsilber Katz, Stettler, & Gurtovenko, 2016;O'Neal & Magai, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the original Gottman et al (1996) manuscript, path analyses incorporated these two distinct dimensions-awareness and coaching-and demonstrated that awareness was a significant predictor of coaching, which was associated directly and indirectly (though other parenting variables) with youth academic achievement, peer relations, and health outcomes. In more recent work (i.e., Katz & Hunter, 2007;Katz, Stettler, & Gurtovenko, 2016), some analyses using the PMEP model have incorporated a third element, acceptance, consisting of parents' acceptance of their own emotion as well as the emotion of their child, which has been positively linked with youth self esteem and negatively associated with depression and internalizing and externalizing symptoms. This body of work demonstrates that awareness and acceptance are important elements in parent-child interactions around emotion, suggesting that mindful parenting, which incorporates both elements, is likely to be associated with ES strategies.…”
Section: Metaemotion Philosophy: Making the Case For Mindful Parentinmentioning
confidence: 99%
“…Accordingly, caregiver emotion coaching has been shown to moderate the association between intimate partner violence exposure and youth internalizing symptoms (Katz & Windecker-Nelson, 2006). Another study with children ages 6–12 years who had been exposed to domestic violence found that mothers' acceptance of their children's anger and sadness during individual parent interviews about the event was related to better anger regulation and fewer depressive symptoms (Katz, Stettler, & Gurtovenko, 2016). In a sample of adolescents living in a high-violence neighborhood, maternal supportive ES behaviors when independently discussing their children's experiences were linked to fewer internalizing and externalizing symptoms (Cunningham, Kliewer, & Garner, 2009).…”
Section: Caregiver Es and Youth Outcomesmentioning
confidence: 99%